2013
DOI: 10.1038/ni.2610
|View full text |Cite
|
Sign up to set email alerts
|

T cell regulation mediated by interaction of soluble CD52 with the inhibitory receptor Siglec-10

Abstract: Functionally diverse T cell populations interact to maintain homeostasis of the immune system. We found that human and mouse antigen-activated T cells with high expression of the lymphocyte surface marker CD52 suppressed other T cells. CD52(hi)CD4(+) T cells were distinct from CD4(+)CD25(+)Foxp3(+) regulatory T cells. Their suppression was mediated by soluble CD52 released by phospholipase C. Soluble CD52 bound to the inhibitory receptor Siglec-10 and impaired phosphorylation of the T cell receptor-associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
151
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(155 citation statements)
references
References 45 publications
3
151
0
1
Order By: Relevance
“…2 Yet another T-cell regulator has recently gained prominence by a recent report in Nature Immunology of CD4 T cells expressing high levels of CD52. 3 CD52 is a short peptide of 12 amino acids in humans linked at its C-terminus to a glycosylphosphatidylinositol (GPI) anchor. Its single N-glycosylation site is occupied by large sialylated polylactossamine on a tetra-antennary fucosylated mannose core.…”
mentioning
confidence: 99%
“…2 Yet another T-cell regulator has recently gained prominence by a recent report in Nature Immunology of CD4 T cells expressing high levels of CD52. 3 CD52 is a short peptide of 12 amino acids in humans linked at its C-terminus to a glycosylphosphatidylinositol (GPI) anchor. Its single N-glycosylation site is occupied by large sialylated polylactossamine on a tetra-antennary fucosylated mannose core.…”
mentioning
confidence: 99%
“…Therefore, it is possible that LGALS3BP could orchestrate the inhibition of different immune cells. Although Siglec-5 is expressed predominantly on myeloid cells such as neutrophils and monocytes/macrophages, Siglec-10 is also expressed on B cells (6,10), and recent evidence suggests that Siglec-10 acts with properly glycosylated CD52 to allow binding and inhibition of T cell activation (51). Moreover, Siglec-9 is expressed on a subpopulation of CD8 T cells (54).…”
Section: Discussionmentioning
confidence: 99%
“…Since it is highly negatively charged it has been supposed that its function consisted in hampering cell adhesion, thus allowing cells to freely move around (see the review of [23]). Although a recent study has found that activated CD4 T cells expressing high levels of CD52 may have regulatory activities on T effector lymphocytes [2] the function of CD52 remains partially unknown.…”
Section: Cd52 the Targetmentioning
confidence: 99%